PROMOTING GUIDED-DISCOVERY LEARNING THROUGH WHATSAPP TO STUDENTS IN OPEN UNIVERSITY - Siti Hadianti; Dewi Wardah Mazidatur Rohmah; Nuraziza Aliah; Sitti Jamilah; Johanna B. S. Pantow (Universitas Terbuka, 2022)
Long-distance learning uses an online platform to transfer the knowledge. It has become a breakthrough in this modern era. The online learning brings many benefits to students, but it is also challenging to be implemented by the tutors in distance education universities. This paper tends to investigate the use of the guided-discovery learning (GDL) method in the psycholinguistics online tutorial class. The participants are the students of the English Education program in Universitas Terbuka, who take Psycholinguistics subject with online tutorial service. The methodology of this research is qualitative by using a case study. The researchers use the WhatsApp application as the platform in conducting the course. The students are required to follow the lesson step by step through WhatsApp. Based on the finding, this research reveals that there are two perspectives of the use of GDL toward psycholinguistics online tutorial class. The first perspective is in students that has two major advantages. The second can be seen from the learning perspective which also has two benefits of the use of GDL.